The Hippo Kinase LATS2 Controls Helicobacter pylori-Induced Epithelial-Mesenchymal Transition and Intestinal Metaplasia in Gastric Mucosa - Molina Castro, Silvia Elena (2020)
Gastric carcinoma is related mostly to CagA+-Helicobacter pylori infection, which disrupts the gastric mucosa turnover and elicits an epithelial-mesenchymal transition (EMT) and preneoplastic transdifferentiation. The tumor suppressor Hippo pathway controls stem cell homeostasis; its core, constituted by the large tumor suppressor 2 (LATS2) kinase and its substrate Yes-associated protein 1 (YAP1), was investigated in this context.